2021
DOI: 10.5867/medwave.2021.05.8210
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior in medical students at a Peruvian public university

Abstract: Introduction Studies show a high prevalence of physical inactivity and sedentary behavior among university students. However, the relationship between physical activity and sedentary behavior in medical students is unknown. Objectives To determine the prevalence of physical activity, sedentary behavior, and related factors among medical students at a public university. Methods We conducted an analytical cross-sectional study that included students from the first to the sixth year of medical school. We used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 0 publications
2
21
0
4
Order By: Relevance
“…2 PA can help reduce the risks of premature death, coronary heart disease, strokes, high blood pressure, a specific form of cancer, type 2 diabetes, osteoporosis, obesity, and weight problems, as well as improve mental health. [3][4][5][6] According to the World Health Organization (WHO), to acquire health benefits, adults aged 18-64 years must accumulate at least 150 minutes of moderate to vigorous intensity PA per week and musclestrengthening activity at least 2 days a week. 1,7 According to literature PA can be divided into occupational, sporting, conditioning, domestic, and other activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 PA can help reduce the risks of premature death, coronary heart disease, strokes, high blood pressure, a specific form of cancer, type 2 diabetes, osteoporosis, obesity, and weight problems, as well as improve mental health. [3][4][5][6] According to the World Health Organization (WHO), to acquire health benefits, adults aged 18-64 years must accumulate at least 150 minutes of moderate to vigorous intensity PA per week and musclestrengthening activity at least 2 days a week. 1,7 According to literature PA can be divided into occupational, sporting, conditioning, domestic, and other activities.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 According to literature PA can be divided into occupational, sporting, conditioning, domestic, and other activities. [3][4][5][6][7] With regard to the country-wise PA status, the Netherlands has the most physically active people, spending over 12 hours a week exercising or participating in sports, followed by Germany and Romania. 8 In 2021, 19.3% of adult Americans were physically active with an average of 5.61 hours per day spent.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Multiple previous studies demonstrated level of PA was not sufficient among students throughout the world. 21,22 In Saudi Arabia, recent literature found that majority of the adolescents including college students were not active to meet the required guidelines for moderate PA. 23 The prevalence of physical inactivity was reported differently in various studies, for instance, it was 34.8% among health care professionals in Saudi Arabia, 24 the highest prevalence of 82.6% was reported among the public in Saudi Arabia 25 while it was 49% among Malaysian medical students. 26 The prevalence of physical activity was measured using the WHO stepwise questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the level of PA reported among university students was low and insufficient ( Rejali & Mostajeran, 2013 ; Janampa-Apaza et al, 2021 ). This may be due to some factors including smoking, overweight and, unhealthy eating habits, and a sedentary lifestyle ( Jiang et al, 2019 ; Lavie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%